Menopausal symptoms in rural middle aged women: a community based cross sectional study - Akhtar, Najma; Gupta, Rajiv K.; Bala, Kiran; Mengi, Vijay; Gupta, Chandni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Menopause poses a big challenge to the healthy aging of a woman. With growing emphasis on universal health coverage and improving quality of life, it is the need of hour to address the issues population of postmenopausal women to enhance our understanding of women’s experiences during menopause. Methods: This cross-sectional study was conducted using non-probability purposive sampling and house-to-house visit in randomly selected villages falling under rural Health Block Kot-Bhalwal. 245 postmenopausal women were interviewed in accordance with pretested questionnaire consisting of Sociodemographic data and Greene Climacteric Scale. Results: Muscle and joint pains was the most common complaint (89.0%), followed by feeling tired or lacking in energy (87.4%), difficulty in sleeping (82.5%) and difficulty in concentrating (80.4%). Nearly three-fourth of the study participants reported to be suffering from Irritability (77.6%), feeling tense/nervous (77.5%), Headaches (76.7%), loss of interest in most things (75.9%), feeling unhappy or depressed (74.29%), sweating at night (73.47%), attacks of anxiety, panic (73.5%), pressure or tightness in head (72.6%), and feeling dizzy or faint (71.8%). Conclusions: A higher prevalence of menopausal symptoms was found. However, more research studies are needed to determine rural urban differences in prevalence and severity of the symptoms using a standardized tool on a larger sample in the community setting.